Mobile Money Services and the Income-Earning of Women Second-hand Cloth Entrepreneurs in Dodoma City - Churk, Josephine P.; Juma, Madina H.; Mpuya, Grace J. (International Review of Management and Marketing, 2023)
The diffusion of mobile money technology has changed the financial landscape across countries in Sub–Saharan Africa, including Tanzania. Women entrepreneurs can use mobile money services to improve business performance by increasing income earning. The study adopted a capability approach to investigate the effect of mobile money services on the income-earning of women’s second-hand cloth entrepreneurs in Dodoma City. Triangulation mixed method was used to collect both qualitative and quantitative data from Sabasaba and Machinga complexes as big market centers. The research surveyed a total of 50 women second-hand cloth entrepreneurs and interviewed 15 key informants. The quantitative data were analyzed by using both descriptive and inferential statistics with the aid of SPSS while qualitative data used content analysis. The result revealed a significant relationship between mobile money saving and the income-earning of women second-hand cloth entrepreneurs. The findings further show that entrepreneurs use informal help groups for borrowing and bank services transactions as coping strategies for solving the challenges of using mobile money services for income earning. The study recommends the collaboration between regulators, entrepreneurs, and private stakeholders to solve challenges that hinder business efforts of increasing income by using mobile money services.